A multifaceted provider-centred intervention versus usual care to improve the recognition and diagnosis of depression in primary health care: a hybrid study - Nogueras, Eva Vanesa; Cantero, Nazaret; Macías, María; Morales-Asencio, José Miguel; García-Herrera Pérez-Bryan, José María; Hurtado, María M. (Cambridge University Press, 2023)
Background: The aim of this study was to evaluate the impact of a multifaceted intervention to implement an adapted guideline for the management of depression in primary health care. Methods: A hybrid trial was carried out to determine the effect of a multicomponent provider centred intervention to improve the detection and diagnosis of depression in primary care, as part of the guideline implementation process, and to collect information about barriers and facilitators in a real-world context. Before the multicomponent intervention, a descriptive cross-sectional study was performed to assess the population prevalence of depression in the participating health centres and to detect possible differences. Subsequently, a quasi experimental two-phase study was carried out with a concurrent control group to assess the impact of the multicomponent intervention on the main outcomes (detection of depression, evaluation of its severity and the use of structured methods to support the diagnosis). Results: Nine-hundred seventy-four patients took part in the first phase. According to their clinical records, the prevalence of depression ranged from 7.2% to 7.9%, and there were no significant differences between the health centres scheduled to receive the intervention and those in the control group. In the experimental phase, 797 randomly selected participants received the multicomponent intervention. Adjusted multivariable analysis performed before the implementation revealed no significant differences in depression between the experimental and control groups. However, after the intervention, modest but significant differences were observed, which persisted at 1 year after the intervention. Conclusions: A multicomponent intervention for the implementation of a clinical guideline for the management of depression in primary care produced improvements in the identification of depression and in the degree of severity recorded.
Keywords: Psicología clínica; Psicosis maniacodepresiva; Depression; Diagnostic tests (PHQ-9); Mood disorder; Mental health; Practice management; Primary care; Psychiatry